2016
DOI: 10.1089/mdr.2015.0205
|View full text |Cite
|
Sign up to set email alerts
|

Emergence ofKlebsiella pneumoniaeST273 CarryingblaNDM-7and ST656 CarryingblaNDM-1in Manila, Philippines

Abstract: We sought to determine the epidemiology of carbapenem-resistant Enterobacteriaceae and to investigate the emergence of carbapenem-resistant Klebsiella pneumoniae in two teaching hospitals in Manila, Philippines. We screened 364 Enterobacteriaceae for carbapenem resistance between 2012 and 2013 and detected four carbapenem-resistant K. pneumoniae isolates from three different patients. We used whole genome sequencing to determine the antibiotic resistance profiles and confirmed the presence of carbapenemase gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…We found that CPE isolates that are often found in clinical settings were also present in the environment. KPC, GES, and OXA-48 producers, which have not yet been detected in clinical settings in the Philippines (14,15,17), were detected in both hospital sewage and river water. Although it is unclear whether these CPE isolates originated from humans or the natural environment, it is possible that they may spread from the natural environment to clinical settings in the future.…”
Section: Resultsmentioning
confidence: 94%
“…We found that CPE isolates that are often found in clinical settings were also present in the environment. KPC, GES, and OXA-48 producers, which have not yet been detected in clinical settings in the Philippines (14,15,17), were detected in both hospital sewage and river water. Although it is unclear whether these CPE isolates originated from humans or the natural environment, it is possible that they may spread from the natural environment to clinical settings in the future.…”
Section: Resultsmentioning
confidence: 94%
“…These different standard sequences have also been obtained elsewhere in the world. The type 273 sequence was found in a strain of K. pneumoniae, isolated from a patient with pneumonia in the Philippines, which carried the blaNDM-7 gene [22]. K. pneumoniae ST 273 has been reported in Italy, Norway, Russia and the United Kingdom.…”
Section: Discussionmentioning
confidence: 98%
“…These isolates corresponded to ST656 and ST392, which have not been previously described in Mexico but which have been described in nosocomial infections in other regions of world. K. pneumoniae ST665 has been described in China and Philippines [31] , [32] as carrying ESBL and carbapenemase genes respectively. In the case of K. pneumoniae , ST392 harbouring KPC-3 and CTX-M alleles has been documented in the United States [33] , [34] .…”
Section: Discussionmentioning
confidence: 99%